2003
DOI: 10.1177/0739456x03022004004
|View full text |Cite
|
Sign up to set email alerts
|

Counterfactual Planning

Abstract: This article uses a specific and long-established planning policy, Seoul's greenbelt, to explore the concept of counterfactual planning. Suppose the greenbelt had never existed. How would the spatial structure of the metropolitan region have been different? Under both monocentric and polycentric assumptions, both population and employment (in terms of densities and numbers) would have been much lower in the core city and the periphery. The effects would have been more dramatic in the core city, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…Scenario N1-S2 shows that a large and wide greenbelt performs better in containing population and jobs within the designated greenbelt boundary. This finding is different from the findings in Bae and Jun (2003) and Freestone (2002), as their research has shown that the greenbelts decentralised population to places beyond the greenbelts while confining jobs in the city centre, which caused a jobs-housing imbalance. The situation in Beijing is different, because without transport improvements, economic activities would not be diverted to new towns easily and a wide greenbelt would still cause overconcentration in the main city.…”
Section: Policy Implicationscontrasting
confidence: 80%
See 2 more Smart Citations
“…Scenario N1-S2 shows that a large and wide greenbelt performs better in containing population and jobs within the designated greenbelt boundary. This finding is different from the findings in Bae and Jun (2003) and Freestone (2002), as their research has shown that the greenbelts decentralised population to places beyond the greenbelts while confining jobs in the city centre, which caused a jobs-housing imbalance. The situation in Beijing is different, because without transport improvements, economic activities would not be diverted to new towns easily and a wide greenbelt would still cause overconcentration in the main city.…”
Section: Policy Implicationscontrasting
confidence: 80%
“…This indicates that the planned greenbelts would bring some negative economic impacts to the city, including decreasing productivity, decreasing household utility, and concentrating residents in the expensive city centre. The effects of increasing population and employment density in the city centre were also found in research done by Bae and Jun (2003) and other studies. For example, Hall (1974) and Evans and Hartwich (2006) found that London's greenbelt increased population density in the main city which pushed housing prices up.…”
Section: Policy Implicationssupporting
confidence: 70%
See 1 more Smart Citation
“…Some researchers agree that the GB policy results in a spatial concentration of development in core cities, and higher densities [30][31][32]. Other researchers, in contrast, have pointed out that the GB brought about leapfrog development by shifting urban development beyond the GB area [10,21,22,33,34]. Unlike the UGB, development in GB lands is strictly prohibited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the absence of the greenbelt policy, the land-use change between 2000 and 2017 can be estimated through various modelling approaches. Most studies measure the effect of an urban containment policy with a greenbelt dummy variable in a regression model [34,39]. For example, Bae and Jun [34] estimate the population and employment density gradients with a greenbelt dummy variable in their model to reallocate jobs and workers in order to measure the effects of Seoul's greenbelt on commuting costs.…”
Section: Modelmentioning
confidence: 99%